Uji Resistensi Nyamuk Aedes aegypty Terhadap Cypermethrin 0,05% di Bandara Sultan Syarif Kasim II Pekanbaru Tahun 2020 - Handayani, Dedes (Pengurus Pusat Ikatan Apoteker Indonesia, 2021)
Dengue Hemorrhagic Fever (DHF) is one vector-borne disease caused by the Aedes aegypti mosquito vector. One way to control the Aedes aegypti mosquito vector is to use insecticides. The insecticide used must be known for its efficacy, safety and resistance status. The use of cypermethrin as an insecticide in controlling the Aedes aegypti mosquito at Sultan Syarif Kasim II Airport Pekanbaru needs to know its resistance status. This study aims to determine the resistance status of the Aedes aegypti mosquito to the insecticide cypermethrin at Sultan Syarif Kasim II Airport, Pekanbaru. The method in this research is descriptive with a cross sectional study design. The independent variable was the Aedes aegypti mosquito exposed to insecticide at Sultan Syarif Kasim II Airport Pekanbaru, while the dependent variable was the Aedes aegypti mosquito susceptibility status. The resistance test method refers to The World Health Organization Susceptibility Test criteria. The resistance test using WHO standard impregnated paper showed that the percentage of mosquito that died after being exposed to impregnated paper containing 0.05% Cypermethrin for 24 hours at Sultan Syarif Kasim II Airport Pekanbaru was 81.5% (Tolerant Phase). There has been a tolerance for the use of 0.05% Cypermethrin against the population of Aedes aegypti mosquitoes in Sultan Syarif Kasim II Airport, Pekanbaru.